Pectoralis Major Myocutaneous Flap versus Free Fasciocutaneous Flap for Reconstruction of Partial Hypopharyngeal Defects: What Should We Be Doing? - Chao, Jerry W.; Spector, Jason A.; Taylor, Erin M.; Otterburn, David M.; Kutler, David I.; Caruana, Salvatore M.; Rohde, Christine H. (Journal of Reconstructive Microsurgery, 2015)
Background Partial hypopharyngeal defects are most commonly reconstructed with the pectoralis major myocutaneous flap (PMMF) or free fasciocutaneous (FFC) flap. The purpose of this study is to determine the ideal method for reconstruction of partial hypopharyngeal defects by reviewing our institutional experience and the literature.Methods A retrospective review of partial hypopharyngeal reconstructions since 2009 was performed. A National Library of Medicine search of studies on partial hypopharyngeal reconstruction since 1988 was performed. Data on complications, diet, and speech were extracted and pooled.Results A total of 18 patients were studied—9 had PMMF reconstruction and 9 had FFC reconstruction. Operative time (8.75 vs. 13.0 hours, p = 0.0003) was shorter in the PMMF group. Pharyngocutaneous fistula developed in one PMMF patient (11.1%) and two FFC patients (22.2%). Late strictures occurred in three PMMF patients. Six patients in each group (66.7%) progressed to a regular diet. Three patients in each group produced tracheoesophageal speech after TEP. Literature review identified 36 relevant studies, with 301 patients reconstructed with PMMF and 605 patients with FFC. Pooled-data analysis revealed that PMMF had higher reported rates of fistula (24.7 vs. 8.9%, p < 0.0001) and requirement for second surgery (11.3 vs. 5.5%, p = 0.04). There was no difference in stricture rates or progression to regular diet. Fewer PMMF patients produced tracheoesophageal speech (17.5 vs. 52.1%, p < 0.0001).Conclusions PMMF and FFC flaps are valid approaches to reconstructing partial hypopharyngeal defects, though rates in the literature of fistula, need for revisional surgery, and tracheoesophageal speech after laryngectomy are more favorable after free flap reconstruction.
Keywords: hypopharynx; reconstruction; pectoralis major flap; free flap